PENGARUH PENEMPATAN, DISIPLIN, DAN PENGALAMAN KERJA PEGAWAI TERHADAP KINERJA PEGAWAI PADA DINAS KOMUNIKASI, INFORMATIKA, STATISTIK DAN PERSANDIAN (KOMINFOSTAN) KABUPATEN DELI SERDANG - Padillah, Putri (CV. Anugerah Duta Perdana, 2025)
This study aims to determine the effect of: Placement on Employee Performance at the Communication, Informatics, Statistics and Cryptography Agency (Kominfostan) of Deli Serdang Regency, Discipline on Employee Performance at the Communication, Informatics, Statistics and Cryptography Agency (Kominfostan) of Deli Serdang Regency. Employee Work Experience on Employee Performance at the Communication, Informatics, Statistics and Cryptography Agency (Kominfostan) of Deli Serdang Regency, Placement, Discipline, and Employee Work Experience on Employee Performance at the Communication, Informatics, Statistics and Cryptography Agency (Kominfostan) of Deli Serdang Regency. The population in this study was all 43 employees at the Communication, Informatics, Statistics and Cryptography Agency (Kominfostan) of Deli Serdang Regency. The data collection method used a questionnaire. Then, validity and reliability tests were carried out. The data analysis techniques used were Descriptive Analysis, multiple linear regression, hypothesis testing, and coefficient of determination. The results of the study indicate that: Placement significantly influences employee performance at the Deli Serdang Regency Communication, Informatics, Statistics, and Cryptography Agency (Kominfostan). Discipline significantly influences employee performance at the Deli Serdang Regency Communication, Informatics, Statistics, and Cryptography Agency (Kominfostan). There is a simultaneous effect of placement, discipline, and employee work experience, amounting to 76.084, on employee performance at the Deli Serdang Regency Communication, Informatics, Statistics, and Cryptography Agency (Kominfostan).